Climate change impacts on snowmelt runoff for mountainous transboundary basins in eastern Turkey. (14th March 2014) - Yucel, Ismail; Güventürk, Abdülkadir; Sen, Omer Lutfi
ABSTRACT This study investigates whether snowmelt runoff for the selected 15 streamflow stations located in the Euphrates, Tigris, Aras, and Çoruh basins in eastern Anatolia, Turkey, has shown a consistent hydrologic response to global climatic changes over the past several decades. It also investigates the future runoff changes in these basins. The analysis utilizes streamflow and meteorological data from 1970 to 2010 available within the study area to identify spatial and temporal patterns of trends in the seasonality of streamflow, temperature, and precipitation. Results indicate significant temperature increases (average 1.3 °C across the stations) over the time period. They also indicate increases in annual precipitation (average 7.5% across the stations) but the increases are not significant, in general. The streamflow timings in the mountainous basins are found to have already shifted to earlier days in the year (9 days on average), and this is a clear indication of earlier spring melting of snowpack due to increasing temperatures in recent years. Eight among fifteen stream gauging stations in the basins show significant time shifts in snowmelt runoff according to statistical trend tests (based on 90% confidence level). A regional climate change simulation based on a high emissions scenario suggests 10–30% declines in the annual surface runoffs of Aras, Euphrates, and Tigris basins and a slight increase (about 4%) in the annual surface runoff of Coruh basin by the end of the present century. It further indicates that the timing of the peak flows will continue to shift earlier (by about 4 weeks over the century) in response to further warming, increasing the fraction of winter runoff while decreasing the fraction of spring runoff in the year in all these basins.